2018
DOI: 10.1039/c8sm01777h
|View full text |Cite
|
Sign up to set email alerts
|

Homodimerization driven self-assembly of glycoluril molecular clips with covalently immobilized poly(ε-caprolactone)

Abstract: We present an unexpected self-assembly of a glycoluril clip-poly(ε-caprolactone) conjugate in chloroform. The conjugate forms homodimer aggregates due to supramolecular interactions between glycoluril moieties, which was confirmed with MALDI-TOF-ms and 1H NMR. TEM revealed the formation of multilayered nanosized prism-shaped objects resembling tree bark in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…These glycoluril clips completely differ in the aspect of homodimerization abilities (Figure S3). Clip 2 exhibits concentration-dependent and thermosensitive behavior of monomer-dimer exchange ,, (Figures S4–S7), whereas for clip 1 the monomer state is favorable independent of its concentration and temperature (Figures S8–S11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These glycoluril clips completely differ in the aspect of homodimerization abilities (Figure S3). Clip 2 exhibits concentration-dependent and thermosensitive behavior of monomer-dimer exchange ,, (Figures S4–S7), whereas for clip 1 the monomer state is favorable independent of its concentration and temperature (Figures S8–S11).…”
Section: Resultsmentioning
confidence: 99%
“…The self-sorting homodimerization and selective host–guest complexation with dihydroxyaromatics of glycoluril clips attracted considerable attention of researchers to tailor novel cross-linked supramolecular materials based on the glycoluril clip homodimers. , Recently, Gosecki et al demonstrated the formation of the first 3D polymer network based on the cross-links built from glycoluril clip homodimers, which were selectively degraded in the presence of resorcinol molecules . For the network construction, a polymer bearing glycoluril clips, equipped with N -(4-methoxyphenyl)­isonicotinamide aromatic sidewalls oriented in the same direction along the glycoluril, was applied.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated a convenient method of glycoluril diester clip derivative, 1 , conversion into a clip with dihydroxylated convex site, 2 (Scheme ) . The choice of glycoluril clip, 1 for building the supramolecular network resulted from its moderate ability to homodimerization along with fast monomer‐dimer exchange rate at room temperature .…”
Section: Resultsmentioning
confidence: 99%
“…Diethanolamide derivative of glycoluril clip, 2 , was prepared according the procedure previously reported . Briefly, diester derivative Glyc Clip (1.277 g; 1.616 mmol) was dissolved in anhydrous DMSO (50 ml) and 2‐ethanolamine (1.974 g; 32.3 mmol) was added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation